Insight into a reversible energy transfer system. Issue 36 (26th August 2016) - Gao, Ming Xuan; Zou, Hong Yan; Gao, Peng Fei; Liu, Yue; Li, Na; Li, Yuan Fang; Huang, Cheng Zhi
Abstract : A novel reversible energy transfer system was constructed in this report, in which two energy transfer processes, nanometal surface energy transfer (NSET) and plasmonic resonance energy transfer (PRET), were coupled in an individual system. It was found that interactions occurred inside this reversible energy transfer system. Abstract : Resonance energy transfer (RET) processes have wide applications; these processes involve a unidirectional energy transfer from a particular donor to a particular acceptor. Here, we report a plasmonic resonance energy transfer (PRET), which occurs from the surface of gold nanoparticles to fluorescent organic dyes, and coexists with a nanometal surface energy transfer (NSET) that operates in the reverse direction. The coexistence of both PRET and NSET in opposite directions means that the roles of both donor and acceptor can be interchanged, which could be identified by using spectrofluorometric measurements and light scattering dark field microscopic imaging. The experimental data could be further theoretically supported using Persson and Lang's model, the quasi-static approximation and finite-difference time-domain simulation. Moreover, disruption of the PRET process by altering the energy transfer pairs suggests that interactions occur inside the reversible energy transfer system, which manifest by increasing the fluorescence quenching efficiency of the NSET process.